Advances in omics research on peanut response to biotic stresses - Huang, Ruihua; Li, Hongqing; Gao, Caiji; Yu, Weichang; Zhang, Shengchun (Frontiers in Plant Science, 2023)
Peanut growth, development, and eventual production are constrained by biotic and abiotic stresses resulting in serious economic losses. To understand the response of peanut to biotic and abiotic stresses and the mechanism of stress tolerance, high-throughput Omics approaches have been used in peanut studies. Integrated Omics approaches are crucial for dissecting the temporal and spatial system-level changes that occur in peanut under various stresses. The integration of functional genomics with other Omics highlights the relationships between peanut genomes and phenotypes under specific stress condition. In this review, we focus on researches on peanut biotic stresses. Reviews on peanut abiotic stresses are presented in other chapters of this issue. Here we review the primary types of biotic stresses that threaten sustainable peanut production, multi-Omics technologies for peanut research and breeding, recent advances in various peanut Omics under biotic stresses, including genomics, transcriptomics, proteomics, metabolomics, miRNAomics, epigenomics and phenomics, the identification of biotic stress-related genes, proteins, metabolites and their networks as well as the development of potential traits. We also discuss the challenges, opportunities, and future directions for peanut Omics under biotic stresses, aiming at sustainable food production. The Omics knowledge is instrumental for improving peanut tolerance to cope with various biotic stresses and for meeting the food demands of the exponentially growing global population.